Gene rearrangements of MLL and RUNX1 sporadically occur in normal CD34+ cells under cytokine stimulation. Issue 5 (14th April 2020) - Harada, Yuka; Shingai, Naoki; Ding, Ye; Sadato, Daichi; Hayashi, Yoshihiro; Yamaguchi, Masaki; Okuyama, Yoshiki; Shimoyama, Tatsu; Ohashi, Kazuteru; Harada, Hironori
Abstract: Gene rearrangements of MLL/KMT2A or RUNX1 are the major cause of therapy‐related leukemia. Moreover, MLL rearrangements are the major cause of infant leukemia, and RUNX1 rearrangements are frequently detected in cord blood. These genes are sensitive to topoisomerase II inhibitors, and various genes have been identified as potential fusion partners. However, fetal exposure to these inhibitors is rare. Therefore, we postulated that even a proliferation signal itself might induce gene rearrangements in hematopoietic stem cells. To test this hypothesis, we detected gene rearrangements in etoposide‐treated or non–treated CD34 + cells cultured with cytokines using inverse PCR. In the etoposide‐treated cells, variable‐sized rearrangement bands were detected in the RUNX1 and MLL genes at 3 hours of culture, which decreased after 7 days. However, more rearrangement bands were detected in the non–treated cells at 7 days of culture. Such gene rearrangements were also detected in peripheral blood stem cells mobilized by cytokines for transplantation. However, none of these rearranged genes encoded the leukemogenic oncogene, and the cells with rearrangements did not expand. These findings suggest that MLL and RUNX1 rearrangements, which occur with very low frequency in normal hematopoietic progenitor cells, may be induced under cytokine stimulation. Most of the cells with gene rearrangements are likely eliminated, except for leukemia‐associated gene rearrangements, resulting in the low prevalence of leukemia development. Abstract : MLL and RUNX1 rearrangements, which occur with very low frequency in normal hematopoietic progenitor cells, may be induced under cytokine stimulation. Most of the cells with gene rearrangements are likely eliminated, except for leukemia‐associated gene rearrangements, resulting in the low prevalence of leukemia development.